Peningkatan Keselamatan Pasien Melalui Sosialisasi Praktik Identifikasi Pasien Kepada Perawat dalam Upaya Menurunkan Kesalahan Medikasi di Ruangan MPKP Kuantan Rumah Sakit Jiwa Tampan Provinsi Riau: Penelitian - Erma Kasumayanti; Endang Mayasari; Dewi Sulastri Juwita; Eva Mayasari (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
Patient safety is a crucial aspect of nursing care quality, particularly in psychiatric hospitals, which face complexities due to communication limitations and fluctuating patient conditions. One common risk is medication errors related to inaccurate patient identification. Observations in the Kuantan MPKP Room, Tampan Mental Hospital, Riau Province, indicate that patient identification prior to medication administration has not been consistently implemented, driven by limited resources in the form of identification labels on medication boxes, as well as suboptimal socialization, supervision, and evaluation of procedure implementation. This Community Service activity aims to improve patient safety by strengthening patient identification practices prior to medication administration. Implementation methods include initial discussions, socialization and simulation of patient identification procedures, provision of photo-based patient identification labels, and monitoring and evaluation through compliance audits. The activity was conducted from December 2 to 11, 2025, involving 14 nurses. The evaluation results showed an increase in nurse compliance, with the majority in the good performance category, as well as optimal utilization of identification facilities. Efforts to reduce the risk of medical errors are carried out through strengthening supervision, providing facilities, and outreach to ensure consistent patient safety practices.